1986
DOI: 10.1007/bf00439234
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome in very low birth weight infants from 1977 to 1983

Abstract: Changes of mortality and neurological morbidity in 351 very low birth-weight infants cared for in the neonatal intensive care unit of the Children's Hospital Tübingen during the years 1977 to 1983 are reported. The main finding was a survival rate increasing from 69.5% in 1977-79 to 76.6% in 1982-83 and a coinciding frequency of severe neurological sequelae decreasing from 9.2%-3.7%. The incidence of minor neurodevelopmental problems remained unchanged. However, mortality after discharge was found to be increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
4

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 15 publications
1
5
1
4
Order By: Relevance
“…The assessment of risk factors in surviving VLBW infants born in the years [1977][1978][1979][1980][1981][1982][1983] showed that the decreasing incidence of neurological handicaps found in this population [5] was accompanied by a decreasing obstetrical and neonatal risk. Evidently, this improvement was facilitated by earlier obstetrical intervention, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of risk factors in surviving VLBW infants born in the years [1977][1978][1979][1980][1981][1982][1983] showed that the decreasing incidence of neurological handicaps found in this population [5] was accompanied by a decreasing obstetrical and neonatal risk. Evidently, this improvement was facilitated by earlier obstetrical intervention, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Children with major handicaps (cerebral palsy, severe mental retardation, severe vision loss, severe hearing loss) and children with normal development were identified in a follow-up study of VLBW infants treated in our NICU during the years 1977-1983 [5].…”
Section: Methodsmentioning
confidence: 99%
“…Da die Tübinger Abteilung in enger Kooperation mit der Abteilung Neonato logie der Klinik über eine dreißigjährige Erfahrungen mit Nachuntersuchungen von Kindern mit neurologischen Auffäl ligkeiten z. T. bis in das Schulalter hinein verfügt [1,10,11,15,16,17] ............................................. .............................................. …”
Section: Strukturierung Der Basisuntersuchungunclassified
“…Reanimation und Transport durch geschutte P~idiater verbessert die Aussichten kl6iner Frfihgeborener betrfichtlich: Sie werden ebenso hfiufig primfir.inmbiert wie im Perinatalzentrum [35] [11]. Vergleichende Langzeituntersuchungen yon in utero-undpostnatal-transportierten Neugeborenen liegen nut von Frfihgeborenen <i006 g vor [17].…”
Section: Qualitiit Yon Reanimation Und Transportunclassified
“…Wiederum sind die Unterschiede bei extrem kleinen Frfihgeborenen nicht immer signifikant. Mit weiterer Abnahme der Sterblichkeit ist jedoch auch bei diesen Kindern ein Effekt des Transportmodus zu erwarten [11].…”
Section: Psychosoziale Aspekte Der Trennung Von Mutter Und Kindunclassified